Gold and silver nanoparticles used for SERS detection of S. aureus and E. coli. (14th April 2020) - Ankamwar, Balaprasad; Gharpure, Saee
Abstract: Surface enhanced Raman scattering (SERS) is emerging as a robust analytical method used in sensing applications in chemical as well as biological systems. SERS has been reported to be used in fast detection of micro-organisms up to the specificity of strain identification. However, use of SERS is tricky because of difficulties involved in selection of SERS active substrate so as to give uniform, sensitive as well as reproducible results. We have synthesized silver and gold nanoparticles using chemical, electrochemical and microwave-assisted methods followed by their characterization. Uses of these nanoparticles in association with micro-organisms such as S. aureus and E. coli have been analyzed using SERS to generate signature spectra. This demonstrates use of so synthesized gold and silver nanoparticles as SERS active substrates for rapid detection of micro-organisms which pave way to find applications in disease diagnostics.